2018
DOI: 10.1371/journal.pone.0192055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self-refraction using a simple device, USee, with manifest refraction in adults

Abstract: BackgroundThe USee device is a new self-refraction tool that allows users to determine their own refractive error. We evaluated the ease of use of USee in adults, and compared the refractive error correction achieved with USee to clinical manifest refraction.MethodsSixty adults with uncorrected visual acuity <20/30 and spherical equivalent between –6.00 and +6.00 diopters completed manifest refraction and self-refraction.ResultsSubjects had a mean (±SD) age of 53.1 (±18.6) years, and 27 (45.0%) were male. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Interestingly, 43.2% of our predictions were within ±0.5D, and 74.0% were within ±1D of the prescription given by an experienced optometrist using subjective refraction. These results are at par with the self-subjective refraction methods, like Eye Netra [32] (38.0% predictions within 0.5D) and USee [4] (77.5% predictions within 1D). Though these results are promising, the mean absolute error of manual retinoscopy (0.18 ± 0.27D) and autorefractor (0.33 ± 0.33D) highlight a scope for improvement (refer to Table 3).…”
Section: Clinical Studysupporting
confidence: 58%
See 2 more Smart Citations
“…Interestingly, 43.2% of our predictions were within ±0.5D, and 74.0% were within ±1D of the prescription given by an experienced optometrist using subjective refraction. These results are at par with the self-subjective refraction methods, like Eye Netra [32] (38.0% predictions within 0.5D) and USee [4] (77.5% predictions within 1D). Though these results are promising, the mean absolute error of manual retinoscopy (0.18 ± 0.27D) and autorefractor (0.33 ± 0.33D) highlight a scope for improvement (refer to Table 3).…”
Section: Clinical Studysupporting
confidence: 58%
“…A scale embedded on the sides of the tube depicts the spherical refractive error. USee [4] is another self-refraction tool. It comprises of a glass frame with an adjustable progressive lens system for each eye placed in front of a 3mm rectangular slit.…”
Section: Self-subjective Refractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study in urban Chinese children similarly found good visual acuity with self-refraction, but greater spherical and cylindrical refractive errors were associated with less accurate results as the range for the devices are limited to −6 to +6 D. Additionally, the adjustable glasses could not correct astigmatism [18]. Adjustable glasses are easy to use as is evident in a study that looked at users of USee which found positive results in 95% of the users [19].…”
Section: Self-adjustable Glassesmentioning
confidence: 99%
“…Thus, they enable the provision of spectacles for children with a difference in prescription in their two eyes which is less than or equal to 1.00 dioptre [19]. It has also been found that they can be dispensed for spherical equivalent of up to ±6.00 dioptres as reported in one of the studies which used a variant of it [20].…”
Section: Introductionmentioning
confidence: 99%